"Miliacin encapsulated by polar lipids stimulates cell proliferation in hair bulb and improves telogen effluvium in women". (28th May 2019) - Keophiphath, Mayoura; Courbière, Christophe; Manzato, Léana; Lamour, Irène; Gaillard, Emmanuelle
Abstract: Background: Miliacin, the main triterpenoid from millet, is known to stimulate keratinocyte metabolism and proliferation. Polar lipids are able to form vesicles with active compounds and to improve their bioavailability. Objectives: We aimed to demonstrate potential benefits of a solution of miliacin encapsulated within polar lipids (MePL) on telogen effluvium prevention and hair condition in women. METHODS: After preliminary cell proliferation studies, a placebo‐controlled, multicentric, randomized, double‐blind trial was performed on sixty‐five nonmenopausal women affected by telogen effluvium, to assess the efficacy of a 12‐week oral supplementation with MePL. Telogen and anagen densities were determined by phototrichogram analysis. Scalp dryness and hair brightness were clinically evaluated using a Likert scale. Results: MePL further enhanced cell proliferation in hair bulb from human scalp than miliacin alone. Compared to the placebo treatment, MePL supplementation significantly reduced telogen density after 12 weeks of treatment. An increase of anagen density was observed in both groups, although there was no significant difference between the two treatments. Scalp dryness was more decreased in the MePL group than in the placebo group. A better improvement of hair brightness was also observed after 12 weeks of supplementation with MePL. Conclusion: Twelve weeks of MePL supplementation significantly reduced the hair density in the telogen phase and, in parallel, improved scalp dryness and hair condition. These effects could be linked to MePL activity on cell proliferation in hair bulb. MePL is an original association of plant extract that could help to prevent and/or limit hair loss in women.